FAKTOR YANG MEMENGARUHI LAMA STUDI MAHASISWA (STUDI KASUS : MAHASISWA PROGRAM SARJANA FAKULTAS MIPA UNIVERSITAS UDAYANA) - IRDIAR, NI PUTU ROSANA PRAMUDITA; SRINADI, I GUSTI AYU MADE; SUSILAWATI, MADE (E-Jurnal Matematika; Vol 13 No 3 (2024), 2024)
This research aims to determine the factors that influence the length of college student study. The method used in this research is Multiple Classification Analysis (MCA). Multiple Classification Analysis (MCA) is a technique for examining the relationship between several independent variables and one dependent variable in the context of an additive model. MCA aims to determine how much influence the independent variables jointly have on the dependent variable and to find out how much influence each independent variable has on the dependent variable either by considering or ignoring the influence of other independent variables. MCA is designed for independent variables measured on a categorical scale, while the dependent variables are measured on a ratio or interval scale. Based on the results of this research, it was found that the factors that influence the length of college student study are gender, area of origin of school, and status of school.